Microwave Assisted Reactions for the Synthesis of 3-Hydrazo Carbonyl-7-Methoxy-1-Tetralone Derivatives - Naidu, A.V.; Dave, M.N. (Asian Journal of Chemistry, 2010)
The present paper discusses microwave assisted reactions for the synthesis of substituted imidazolines (IIa-g) from the condensation reaction of 3-hydraw carbonyl-7 -methoxy-1-tetralone (I) and substituted oxazolinones, and synthesis of substituted quinazolin-4(3H)ones (IIIa-b) from the condensation reaction of (I) and substituted benzoxazones.